Quality of sleep in a sample of Egyptian medical students. Issue 4 (October 2016) - Elwasify, Mohamed; Barakat, Doaa H.; Fawzy, Mohamed; Elwasify, Mahmoud; Rashed, Ibrahem; Radwan, Doaa N.
Abstract : Background: In the last few years, there has been a growing attention to sleep and related disorders. Numerous studies conducted within the past decade have analyzed the deleterious effects of poor sleep quality on university students and medical staff in various specialties, but only few studies have been conducted in the Middle East. Aim: The aim of the study was to investigate the prevalence of poor sleep quality among (a sample of) Egyptian medical students. Participants and methods: This cross-sectional, questionnaire-based, observational study was conducted during the period from April to June 2015 on 1182 undergraduate medical students from Assiut and Mansoura Universities in Egypt. The data were gathered using a sociodemographic questionnaire and Pittsburgh Sleep Quality Index (PSQI), and were analyzed using the SPSS software. Results: Mean PSQI score was 6.01 (SD±2.73). According to the PSQI, 46.7% of the subjects had good sleep quality and 53.3% had poor sleep quality. Poor sleep quality was mostly prevalent among those in the early years of medical education, caffeine consumers, cigarette smokers, those with fairly bad and very bad subjective sleep quality, those with sleep latency above 30 min, sleep duration less than 7 h, fairly bad and very bad daytime functioning, those taking sleep medications, and those with sleep disturbance, and sleep efficiency below 85%. Conclusion: Poor sleep quality is highly prevalent among medical students in Egypt.